A Qualitative Case Study of Childhood Trauma Recovery Through Trauma-Informed Counseling, Spiritual Cognitive Restructuring, and Gradual Exposure - Sugandi Miharja; Muhammad Saffuan Abdullah; Chika Lestari; Azizah Abd Ghani; Iyad Muayid Salaf (Grief and Trauma, 2026)
Childhood trauma can significantly affect emotional development and behavioral functioning, particularly when traumatic experiences become associated with specific environments or situations. Situational trauma may lead to persistent fear responses and avoidance behaviors that interfere with children’s daily activities. Despite extensive research on cognitive behavioral therapy and exposure-based interventions for anxiety disorders, limited studies have explored the subjective process of childhood trauma recovery using qualitative approaches. This study aims to examine the psychological recovery process of a child experiencing elevator-related situational phobia following a traumatic incident of being trapped inside an elevator. A qualitative case study design was employed using continuous observation and in-depth interviews conducted over a 93-day intervention period. Data were collected through semi-structured interviews with the client and parents, participant observation during counseling sessions and exposure activities, and reflective documentation throughout the intervention process. The data were analyzed using thematic analysis to identify patterns of psychological change during recovery. The findings reveal that trauma recovery occurred through six interconnected phases: initial fear and avoidance, development of emotional regulation, cognitive restructuring of fear, gradual exposure and confidence building, spiritual meaning and trust, and behavioral reintegration. These results suggest that effective childhood trauma recovery involves an integrative process combining emotional stabilization, cognitive reinterpretation, behavioral exposure, and spiritual coping. The study highlights the importance of holistic and culturally sensitive counseling approaches in facilitating trauma recovery among children experiencing situational fear